Gereja Metaverse dan Aspek Kosmis dari Sang Anak Domba: Tinjauan Kritis Gereja Metaverse berdasarkan Aspek Kosmis dari Anak Domba yang Terdapat dalam Wahyu Pasal 5 - Jammes Takaliuang; Gerald Moratua Siregar (Institut Injil Indonesia, 2023)
The metaverse Church is a virtual reality church that exists to respond to the demands of these days work culture that is all digital, instant, individualistic, practical, and pragmatic. For the reason of effectiveness and time efficiency, some church members today seem to be starting to shift from conventional models of worship to the virtual church model. But, is virtual reality church theologically correct? This article will discuss the advantages and disadvantages of virtual church reality based on the theological foundations found in The Book of Revelation chapter 5 which contains the cosmic aspect of Christ. This article uses two research methodologies, namely the qualitative literature research method and the biblical interpretation methodology. Through this writing, readers are expected to be able to understand some of the advantages and disadvantages of virtual reality churches.